A suggested strategy for Developing Assessment Processes and observing Professional Growth of Educational and Specialist Superintendents " a field study on the level of the Ministry of Education in Syrian Arab Republic" (Journal of Hama University, 2021)
The study aimed at arranging the problems of evaluating and following up the professional growth of the performance of educational counselors and specialist from the point of view of a sample of them, examining the differences in trends according to a set taxonomic variables and developing a proposed strategy to develop evaluation and follow up processors for the professional growth and educational matters in light of the results of study, and in the light of the experiences of some countries. The study was applied on a sample consisting of (240) individuals working as ( educational instructors) chosen from (6) directorates of education in the governorates ( Damascus, Rural Damascus, Lattakia, Sweida, Aleppo) and (30) specialist instructors from the education of Damascus countryside.A questionnaire was designed to measure the attitude of educational mentors and specialists towards the problems of evaluating and following their professional growth, and it included (50) items distributed equally into (5) sub- domains and the validity and reliability of the questionnaire on the local environment was verified, and the results showed that the ascending order of the problems of evaluating and following up the professional growth of the performance of educational counselors and specialists according to their relative importance from the point of view of a sample of them was arranged as follows ( evaluation problems related to the factors. Personally academic qualification evaluation problems, personal traits assessment problems, evaluation problems related to administrative aspects, practical and professional experience evaluation problems). The result showed that there were no significant differences in the trends of educational mentors and specialist sample towards the problems of assessing and follow up their professional growth for each sub-field and for the overall degree according to the title variable ( educational mentor, specialist mentor), as well as differences in the trend of each sub-field and for the total degree according to the scientific qualification variable differences were in favor of those with higher academic qualifications, and according to variable years of experience, the differences were in favor of educational mentor specialists with greater years of experience, and the study also concluded that a process strategy was developed to develop evaluation and follow up processes for the professional growth of educational mentors and specialists in the light of field results, and in the light of experiences of some countries.